Consolidated Foreign Wealth of Nations: Initial steps and novel estimates - Sanchez Pacheco, Andre (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
This thesis is made of three essays in International Macroeconomics. The central question these essays focus on is how to assess the international exposure of countries. The conventional approach uses the residence of the immediate counterparts as the key criterion in sorting these balance sheet exposures. However, this approach presents shortcomings that make it difficult for policymakers and researchers to sort the ultimate exposure countries have to financial risks. In this thesis, I construct novel estimates on the international exposure of countries based on a consolidated-by-nationality approach. These estimates are used to analyse global profit shifting activities and the spillovers of U.S. monetary policy shocks on multinational enterprises. The first essay studies the link between U.S. international financial integration and tax differentials. In particular, we document a robust relation between corporate tax differentials and U.S. international financial integration (IFI). While this is the case for traditional IFI based on cross-border positions, the positive link also emerges for its larger consolidated-by-nationality version. The gap between these IFI measures, the key outcome variable in our analysis, exhibits a strong positive correlation with tax differentials too. This is in part due to consolidated assets of multinational enterprises being more strongly correlated with tax differentials than their cross-border counterpart. We interpret this as indirect evidence of U.S. multinationals taking advantage of tax differentials in ways that go beyond what is captured by traditional Balance of Payments procedures. The second essay seeks to assess how exposed Ireland is to foreign shocks. Relying on residence-based measures of foreign holdings to answer this question can be challenging. These statistics are obscured by the vast presence of Special Purpose Entities in the country. Alternatively, I construct an estimate of the Irish consolidated-by-nationality foreign balance sheet for the period between 2011 and 2019 based on a novel methodology that builds on firm-level data. I find that Ireland's consolidated foreign balance sheet is on average 46.7\% smaller relative to its residence-based analogue. I interpret this result as an indication that Ireland is significantly less exposed to foreign shocks than what is suggested by residence-based statistics. Lastly, the third essay presents novel estimates of foreign holdings from a consolidated-by-nationality perspective for a sample of fourteen developed countries over multiple years. It describes the stylized facts that emerge from this new data-set on the international exposure of countries. It shows that aggregate international financial integration is larger from a nationality-based approach relative to the conventional residence-based data. These novel data are used to analyze (1) profit shifting activities and (2) spillovers from U.S. monetary policy shocks. I find evidence suggesting that nationals of relatively high-tax countries may shift assets to low-tax countries in ways not fully captured in residence-based statistics. I also find that a tightening in U.S. monetary policy is associated with a decline in consolidated-by-nationality foreign asset holdings by non-financial multinational enterprises. Such findings highlight the usefulness of this new data-set in international macroeconomics.
APPROVED
Keywords: International financial integration; Financial globalisation; Consolidated-by-nationality statistics